Antioxidant Activity of Milk Fermented With Lactobacillus Plantarum and Leuconostoc Mesenteroides Isolated From Non-Dairy Sources - Abubakr, Maryam A. S.; Hassan, Zaiton; Salem, Galia (Asian Journal of Pharmaceutical Research and Development, 2018)
The aim of this study was to evaluate the antioxidant activity of skim milk hydrolysate fermented with lactobacilli isolated from nondairy sources as determined by 1, 1-diphenyl-2-picrylhydrazyl (DPPH) assay, ferrous chelating activity (FCA) and reducing power (RP). The values of DPPH, FCA and RP increased with concentration of skim milk hydrolysate (SMH) and varied LAB isolates. The DPPH IC50 values of SMH fermented with Lb. plantarum1 was higher (2.92 mg/ml) than Ln. mesenteroides and Lb. plantarum ATCC8014. While, the IC50 values of SMH fermented with Lb. plantarum 1 and Ln. mesenteroides were 0.46 and 0.69 mg/ml, respectively greater than Lb. plantarum ATCC8014 (IC50 value 0.74 mg/ml) but lower than EDTA. All isolates showed poor reducing power compared to ascorbic acid. Among the LAB isolates Lb. plantarum ATCC8014 and Ln. mesenteroides seemed to generate peptides with similar reducing power activity. Lb. plantarum1 and Ln. mesenteroides isolated from non-dairy sources have probiotic properties and antioxidative properties which could benefit consumers.